2012
DOI: 10.25011/cim.v35i4.17147
|View full text |Cite
|
Sign up to set email alerts
|

Current research status of endoscopic submucosal dissection for colorectal neoplasms

Abstract: Endoscopic submucosal dissection (ESD) has been applied to, and gradually standardized for, early gastric cancers; however, it has not yet been widely used for treatment of colorectal neoplasms. Compared with gastric ESD, the thinner colorectal wall and winding nature of the colon make colorectal ESD a much more difficult operative technique. Despite greater risks of postoperative complications, particularly perforation of the colon, more and more endoscopists are making an effort to study this new technique i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Endoscopic submucosal dissection (ESD) may overcome this problem, allowing dissection of larger lesions in one piece. However, the procedure is technically difficult, time-consuming, associated with hospital admission and has an increased risk of complications such bleeding or perforation [11]. A recent review evaluating the efficacy of EMR and ESD for LSTs noted that overall polyp recurrence occurred more frequently with EMR (12.6%) compared to ESD (1.1 %).…”
Section: Introductionmentioning
confidence: 99%
“…Endoscopic submucosal dissection (ESD) may overcome this problem, allowing dissection of larger lesions in one piece. However, the procedure is technically difficult, time-consuming, associated with hospital admission and has an increased risk of complications such bleeding or perforation [11]. A recent review evaluating the efficacy of EMR and ESD for LSTs noted that overall polyp recurrence occurred more frequently with EMR (12.6%) compared to ESD (1.1 %).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, because of the tenuity of the colorectal wall, colorectal ESD has a higher risk of perforation than gastric ESD. 30 Several studies reported perforation rates of 1.4-10.4% in colorectal ESD. 31 The majority of cases were treated successfully by conservative management without emergency surgery and small perforations were closed by endoscopic clipping.…”
Section: Discussionmentioning
confidence: 99%
“…inflammatory diseases such as ulcerative colitis; and non disseminated carcinoma that was not successfully removed after endoscopic mucosal resection (17). Regarding malignant lesions, mucosal neoplasms or carcinomas with superficial (< 1,000 μm) submucosal invasion without lymphovascular invasion are amenable to ESD as well (18,19).…”
Section: A B C D E Fmentioning
confidence: 99%